Peripheral mononuclear leucocyte beta adrenoceptors and non-specific bronchial responsiveness to methacholine in young and elderly normal subjects and asthmatic patients. - Connolly, M. J. (1994)
BACKGROUND--As beta adrenoceptor dysfunction occurs in both the normal elderly subject and in young asthmatic patients, the hypothesis was examined that age related beta adrenoceptor changes are important in the pathogenesis of late onset asthma in old age. METHODS--Subjects were non-smokers who comprised 17 young normal subjects of mean (SE) age 29.4 (1.3) years, 17 elderly normal subjects of 67.2 (1.3) years, seven young asthmatic patients of 31.0 (2.8) years, and 17 elderly asthmatic patients of 68.5 (1.4) years. All asthmatic patients withheld inhalers for 12 hours and oral treatment for 24 hours before each study day. Subjects underwent an inhaled methacholine challenge (Newcastle dosimeter method) on two nonconsecutive days. The slope of the flow at 50% of the vital capacity (FEF50) dose-response curve was derived from the percentage fall in FEE50 divided by methacholine dose (sFEF50). Beta-adrenoceptor density (Bmax) and affinity (%KH) were determined with (125I)iodocyanopindolol as the radioligand in membranes prepared from mononuclear leucocytes. RESULTS--Log sFEF50 was shown to be reproducible (repeatability coefficient 0.41) on the two study days and was inversely related to %KH but not to Bmax. Multiple regression analysis (all 58 subjects, overall R2 = 0.57) revealed an inverse relation between log sFEF50 and %KH, and between log sFEF50 and Bmax. The inverse relation between log sFEF50 and %KH was preserved whereas that between log sFEF50 and Bmax was lost when young asthmatic subjects or when all asthmatic subjects were excluded from multiple regression analysis. CONCLUSIONS--The beta adrenoceptor dysfunction observed in late onset asthma may be similar to that seen during ageing. Thus late onset asthma may represent the extreme of a spectrum of age associated beta adrenoceptor dysfunction.